ЛІКУВАЛЬНА ПЕДАГОГІКА ПРИ НЕВРОЛОГІЧЙИХ ТА ПСИХІЧНИХ ЗАХВОРЮВАННЯХ ДІТЕЙ (Педагогіка вищої та середньої школи, 2008)
In this article are risen the questions of the therapeutic pedagogy for the pupils with limited possibilities and suffering from nervous and mentally diseases.